2021
DOI: 10.22541/au.162699252.29324612/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pediatric asthma control during the COVID-19 pandemic: a systematic review and meta-analysis

Abstract: Background: During the current ongoing COVID-19 pandemic, studies had reported that patients with asthma would experience increased asthma-associated morbidity because of the respiratory virus SARS-CoV-2 infection, based on experience with other respiratory viral infections. However, some studies suggested that there was no apparent increase in asthma related morbidity in children with asthma, it is even possible that due to reduced exposures due to confinement, such children may have improved outcomes. In ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Although there were detrimental effects on children and young people's physical and mental well-being during the pandemic, some studies reported improvements in seasonal respiratory allergy symptom control, particularly during lockdown measures. 52,53 Nonpharmaceutical interventions, such as handwashing, masks, and social/physical distancing, reduction in the concentrations of traffic-related air pollutants 54,55 and decline in other respiratory infections incidence, may have contributed to reduced impact on allergic disease 56,57 particularly respiratory, [58][59][60][61][62][63] number of exacerbations 59,62,[64][65][66][67][68][69][70][71] and the odds of emergency room visit and/ or hospital admissions. 59,66,[72][73][74][75][76][77][78] Improvements were normally associated with time spent at home, and stronger effects were found in some studies among individuals with severe disease.…”
Section: Are There Any Known Benefits and Harms Of Lockdown Measures ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although there were detrimental effects on children and young people's physical and mental well-being during the pandemic, some studies reported improvements in seasonal respiratory allergy symptom control, particularly during lockdown measures. 52,53 Nonpharmaceutical interventions, such as handwashing, masks, and social/physical distancing, reduction in the concentrations of traffic-related air pollutants 54,55 and decline in other respiratory infections incidence, may have contributed to reduced impact on allergic disease 56,57 particularly respiratory, [58][59][60][61][62][63] number of exacerbations 59,62,[64][65][66][67][68][69][70][71] and the odds of emergency room visit and/ or hospital admissions. 59,66,[72][73][74][75][76][77][78] Improvements were normally associated with time spent at home, and stronger effects were found in some studies among individuals with severe disease.…”
Section: Are There Any Known Benefits and Harms Of Lockdown Measures ...mentioning
confidence: 99%
“…52,53 Nonpharmaceutical interventions, such as handwashing, masks, and social/physical distancing, reduction in the concentrations of traffic-related air pollutants 54,55 and decline in other respiratory infections incidence, may have contributed to reduced impact on allergic disease 56,57 particularly respiratory, [58][59][60][61][62][63] number of exacerbations 59,62,[64][65][66][67][68][69][70][71] and the odds of emergency room visit and/ or hospital admissions. 59,66,[72][73][74][75][76][77][78] Improvements were normally associated with time spent at home, and stronger effects were found in some studies among individuals with severe disease. 52 Despite strong associations of lockdown measures and improvements in allergic children, anxiety levels and perceptions of elevated health risk were increased among carers, 79 regardless of the actual health state of the child.…”
Section: Are There Any Known Benefits and Harms Of Lockdown Measures ...mentioning
confidence: 99%
“…Many have speculated about the potential drivers of observed improvements in youth asthma functioning throughout the course of the pandemic. Hypothesized contributors to improvements include increased adherence to asthma medications, avoidance of the healthcare setting due to fear of contracting COVID-19, improved air quality due to school closures and "work-fromhome" regulations, decreased participation in physical activity outside of the home, decreased exposure to asthma triggers, and decreased potential for viral exposure due to nationwide lockdowns (2,3,7). Additionally, families may have engaged in preventative measures for asthma management following the onset of the pandemic (i.e., refilling prescriptions, coordinating telehealth specialty care appointments) to avoid lapses in care during the healthcare state of emergency.…”
Section: Introductionmentioning
confidence: 99%